The utilization of family planning among women of reproductive age attending a teaching hospital, Oyo State, Nigeria - Olajide et al. (Rwanda Medical Journal)
INTRODUCTION: The utilization of family planning services among women of reproductive age is essential and underscores the need for comprehensive health education and accessible family planning services. This study assessed sociodemographic factors influencing the utilization of family planning among women attending a teaching hospital in Oyo State, Nigeria.